Bioactive terpenoids from Santalum album derived endophytic fungus Fusarium sp. YD-2. Issue 27 (19th April 2018) - Yan, Chong; Liu, Weiyang; Li, Jing; Deng, Yanlian; Chen, Senhua; Liu, Hongju
Abstract : Two new spiromeroterpenoids, namely fusariumin A (1 ) and B (2 ), along with four known terpenoids, asperterpenoid A (3 ), agathic acid (4 ), guignardone N (5 ), and trametenolic acid (6 ), were obtained from the endophytic fungus Fusarium sp. YD-2, derived from the twigs of Santalum album . Abstract : Two new spiromeroterpenoids, namely fusariumin A (1 ) and B (2 ), along with four known terpenoids, asperterpenoid A (3 ), agathic acid (4 ), guignardone N (5 ), and trametenolic acid (6 ), were obtained from the endophytic fungus Fusarium sp. YD-2, derived from the twigs of Santalum album . Their structures were elucidated by a combination of spectroscopic analyses. The absolute configuration of1 was determined by single-crystal X-ray diffraction using Cu Kα radiation, and that of2 was elucidated on the basis of experimental and calculated electronic circular dichroism spectra. Compound2 exhibited moderate anti-inflammatory activity in vitro by inhibiting nitric oxide (NO) production in lipopolysaccharide activated RAW264.7 cells with an IC50 value of 50 μM, and compound3 showed strong anti-inflammatory activity with an IC50 value of 1.6 μM. In the antibacterial assay, compound1 displayed significant activities against Staphylococcus aureus and Pseudomonas aeruginosa with an MIC value of 6.3 μg mL −1, and compound3 showed moderate activities against Salmonella enteritidis and Micrococcus luteus with MIC values of 6.3 and 25.2 μg mL −1, respectively.